The effects of income on demand for food in poor countries: are our food consumption databases giving us reliable estimates? - Bouis, Howarth E. (Elsevier, 1994)
Cross-section estimates of income elasticities for food staples in the aggregate based on quantity information from household food expenditure surveys are often in the 0.3 0.6 range. It is shown that differences in per capita calorie intakes across income groups implied by these income elasticities are grossly inconsistent with observed differences in bodyweights. Moreover, time series data frequently indicate that national per capita consumption of food staples in the aggregate remains constant even as per capita gross national product rises substantially. Cross-section income elasticity estimates are biased upwards due to the failure of food expenditure surveys to undertake an accurate accounting of food transfers from high to low income groups, biases which are not generated by survey techniques which record food intakes directly.